The interaction between reflective processing and language among bilingual speakers - Poh, Wei Lin (2017)
Internal or Reflective attention can refer to our thoughts/reflections in order to make sense of our external world through our senses and perception. Reflective attention also includes the act of refreshing which is the act of thinking back and shifting internal attention towards previously activated mental representations. Previous research (M.R. Johnson et al., 2013) has shown that refreshing mirrors a striking similarity to that of inhibition of return (IOR) effect which inhibits visual attention to return to a previously cued location (Posner & Cohen, 1984; Posner, Rafal, Choate, & Vaughan, 1985). This IOR-like mechanism helps facilitate our thoughts (similarly to perception) by encouraging internal attention to move towards new information and avoid constant fixation on a single thought (M.R. Johnson et al., 2013) which was coined as reflective IOR (rIOR). The objective of the thesis investigates variables such as time duration and language during the production of rIOR mechanism.